MENGOPTIMALKAN POTENSI OTAK KANAN SISWA DALAM PEMBELAJARAN KIMIA - Ikhwan Khairu Sadiqin; Maya Istyadji; Atiek Winarti (Universitas Lambung Mangkurat, 2017)
Abstract. Chemical learning for students in schools tends to focus on the performance of the left brain only. Motivation to learn to be low. Another impact is students have difficulty in understanding the concept of chemistry that is generally abstract. Concepts of chemistry is abstract, include depiction of space (macroscopic and microscopic) and symbolic. This chemical characteristic is closely related to right-brain intelligence that tend to be artistic feeling, color sensitivity, space depiction, symbolic, synthesis and creation. Therefore the learning of chemistry requires the optimal potential of both parts of the brain, left and right hemisphere. Implementation of brain based learning is a concrete solution to optimize the performance of left and right hemisphere of students in chemistry learning activities.Keywords: right brain, brain based learning, motivation